Alcohol drinking and cutaneous melanoma risk: a systematic review and dose–risk meta‐analysis3. (May 2014) - Rota, M.; Pasquali, E.; Bellocco, R.; Bagnardi, V.; Scotti, L.; Islami, F.; Negri, E.; Boffetta, P.; Pelucchi, C.; Corrao, G.; La Vecchia, C.
Summary It has been suggested that alcohol intake increases sunburn severity, a major risk factor for cutaneous melanoma (CM). Several epidemiological studies have investigated the relationship between alcohol consumption and CM, but the evidence is inconsistent. Therefore, we aimed to quantify this relationship better, using a meta‐analytical approach. The dose–risk relationship was also modelled through a class of flexible nonlinear meta‐regression random effects models. The present meta‐analysis included 16 studies (14 case–control and two cohort investigations) with a total of 6251 cases of CM. The pooled relative risk (RR) for any alcohol drinking compared with no/occasional drinking was 1·20 [95% confidence interval (CI) 1·06–1·37]. The risk estimate was similar in case–control (RR 1·20, 95% CI 1·01–1·44) and cohort studies (RR 1·26, 95% CI 1·19–1·35). The pooled RR was 1·10 (95% CI 0·96–1·26) for light alcohol drinking (≤ 1 drink per day) and 1·18 (95% CI 1·01–1·40) for moderate‐to‐heavy drinking. The pooled RR from 10 studies adjusting for sun exposure was 1·15 (95% CI 0·94–1·41), while the RR from six unadjusted studies was 1·27 (95% CI 1·20–1·35). No evidence of publication bias was detected. This meta‐analysis of published data reveals that alcohol consumption is positively associated with the risk of CM. However, caution in interpreting these results is required, as residual confounding by sun exposure cannot be ruled out.